Safety of ozanimod and etrasimod in ulcerative colitis - Long Chen; Dongping Wan; Benkai Xing; Xiaohui Ji; Wenyan Zhou; Yanbing Liu; Yongchao Lu (Medicine, 2026)
Ozanimod and etrasimod are sphingosine-1-phosphate receptor modulators approved for ulcerative colitis treatment. Given their limited real-world safety data in this specific population, we conducted a disproportionality analysis using the Food and Drug Administration Adverse Event (AE) Reporting System database, aiming to explore their post-marketing safety profile. Original data were extracted from the aforementioned database. Three algorithms, namely reporting odds ratio, proportional reporting ratio, and Bayesian confidence propagation neural network, were employed to identify drug-related AE signals. We retrieved 1632 reports for ozanimod and 283 for etrasimod, with the most frequently reported age group being 50 to 59 years in both groups. At the system organ class level, signals for nervous system disorders, eye disorders, and cardiac disorders were detected for both drugs. At the preferred term level, 75 positive signals were identified for ozanimod and 24 for etrasimod. Common AEs for both drugs included drug ineffective, headache, dizziness, nausea, and blurred vision. Although most findings were consistent with the prescribing information, several unexpected AEs related to ozanimod merit special attention. The median onset time for ozanimod-related AEs was 17.5 days (interquartile range: 1.5–87.5 days). For etrasimod, the median onset time of AEs was 17.5 days (interquartile range: 2.75–69.25 days). We hope that these findings can provide comprehensive safety evidence for ozanimod and etrasimod, serving as a reference for clinicians in their individualized and safe application. However, due to the inherent limitations of the database, these findings still require further validation through prospective studies.